ANALISIS MANAJEMEN RISIKO OPERASIONAL BONGKAR MUAT MENGGUNAKAN METODE HOR - Salim, Siti Rofifa; Herlina, Herlina (Universitas Majalengka, 2024)
This research focuses on risk management in loading and unloading operations at SPMT Jamrud Nilam Mirah Branch, a multipurposeterminal in Surabaya. The aim of this research is to analyze risk events and their causes using the house of risk method, with a focus on determining risk agent priorities and mitigation strategies. In dry bulk cargo loading unloading operations, there are 36 risk events and 23 risk agent identified, with three dominant risk agent; lack of operator alertness, dust spills of hazardous bulk commodities and working at height, and slippery conditions. Based on these risk agents, shix key mitigation strategies were identified, which significantly reduced the estimated time of delay by 63% of the total cumulative ETD value. These strategies include the implementation of automatic warningsystems, the application of 3D technology, continuous risk monitoring and analysis system, anonymous reporting, the use of drones, and the use of predictive algorithms.